STRATEGI KEPALA SEKOLAH DALAM MANAJEMEN PENDIDIKAN ISLAM UNTUK MENINGKATKAN DISIPLIN DAN AKHLAK SISWA DI SMP NEGERI 1 PORTIBI - Ulfa Hayana Sari Harahap; Syafri Fadillah Marpaung (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the principal’s strategies in Islamic education management to improve students’ discipline and moral character at SMP Negeri 1 Portibi. The study was motivated by the persistence of disciplinary problems and the low level of students’ moral awareness, which require systematic and continuous guidance through school policies based on Islamic values. Methods: This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving the principal, teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. Results The findings revealed that the principal implemented strategies through religious programs, habituation of religious practices, enforcement of school regulations, teachers’ role modeling, and periodic evaluations. These strategies positively contributed to improving students’ discipline, politeness, and awareness of worship. Novelty: his study provides an empirical and comprehensive analysis of the implementation of Islamic education management in fostering students’ discipline and moral character in a public junior high school context.